If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -8) + 90 = 180 Reorder the terms: (-8 + 2x) + 90 = 180 Remove parenthesis around (-8 + 2x) -8 + 2x + 90 = 180 Reorder the terms: -8 + 90 + 2x = 180 Combine like terms: -8 + 90 = 82 82 + 2x = 180 Solving 82 + 2x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-82' to each side of the equation. 82 + -82 + 2x = 180 + -82 Combine like terms: 82 + -82 = 0 0 + 2x = 180 + -82 2x = 180 + -82 Combine like terms: 180 + -82 = 98 2x = 98 Divide each side by '2'. x = 49 Simplifying x = 49
| 10(324)+14K= | | 8y+44=4y | | 10(243)+14K= | | 2m^2+7m+6=0 | | 3=-16t^2+4t | | (3x+51)+37+x=180 | | T+K=243 | | 2x-10=25 | | 650+30(n-10)= | | 3/4(m-6)=-2 | | 3/4(m-6)=2 | | 1x^2+1+1x^2=5 | | m^2+20m-300=0 | | 1.5y=6 | | n+4N=245 | | k^2-13k+12=0 | | -3p+7=5-(5p+7) | | (3)2X+3Y=75.75 | | (-2)3X+2Y=79.40 | | 174=15x+4X^2 | | -3x-2y-x-5xy+3= | | 6.4+7x(2)=10.9-6x | | 3S+2J=75.78 | | -2x+4=7x-3 | | 6x^2-7-20=0 | | 5x+1=-6x-8 | | -8.2x=65.6 | | 3S+2J=79.40 | | 12(x+3)=3(4x+3)+27 | | -3x-7=x+4 | | -.25(x-8)+.5(x+2)=x+15 | | n^2+7n-60=0 |